2022
DOI: 10.5037/jomr.2022.13101
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Alveolar Ridge Augmentation with Autogenous Tooth Block Graft Compared with Autogenous Bone Block Graft: a Systematic Review

Abstract: Objectives:The objective of the present systematic review was to evaluate the current knowledge of implant treatment outcome following lateral alveolar ridge augmentation with autogenous tooth block graft compared with autogenous bone block graft prior to implant placement. Material and Methods: MEDLINE (PubMed), Embase and Cochrane Library search in combination with hand-search of relevant journals was conducted including human studies published in English through December 20, 2021. Comparative and non-compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The physical-chemical and biochemical features of the dentin and enamel matrix obtained after processing teeth derivatives with the Tooth Transformer device have been described in a recent in vitro study [14][15][16][17][18][19][20][21][22][23][24][25]. A study [22] found that the biocompatibility of demineralized dentin is even higher than the more popular xenograft bovine bone, and that demineralization increases BMP-2 and type I collagen bioavailability as compared with non-demineralized tooth derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical-chemical and biochemical features of the dentin and enamel matrix obtained after processing teeth derivatives with the Tooth Transformer device have been described in a recent in vitro study [14][15][16][17][18][19][20][21][22][23][24][25]. A study [22] found that the biocompatibility of demineralized dentin is even higher than the more popular xenograft bovine bone, and that demineralization increases BMP-2 and type I collagen bioavailability as compared with non-demineralized tooth derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth extraction is certainly the most performed surgical procedure in dentistry, and the teeth extracted were considered waste elements. Recent clinical studies have proposed the reimplantation of the same dental elements, the partial retention of the root to allow for the preservation of the bundle bone, and the use of particulate dentin as a graft material [11][12][13][14][15][16][17][18][19][20]. Studies in humans have demonstrated the clinical efficacy and safety of the partially demineralized autogenous dentine matrix prepared chairside as a bone graft [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneity prevents most of them from conducting a meta-analysis to determine the extent of this graft's effectiveness. In this umbrella review, 9 15 16 17 18 19 20 21 22 23 systematic/meta-analysis articles comprising 81 (23 RCTs and 58 non-RCTs) articles were included. The outcomes extracted from these umbrella studies were associated with tooth graft procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher incidence of short-term peri-implantitis was observed after LARA with autogenous tooth block grafting. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation